Implementasi Sistem Monitoring Level Air Real-Time Berbasis Web - M. Dimas Kautsar; Muh Firizki; Eka Puji Widianto (MDP Student Conference, 2026)
Manual water level monitoring is ineffective and unable to provide real-time data. This study develops an Internet of Things-based water level monitoring system using ESP32 and HC-SR04 ultrasonic sensor to monitor water height in a 1200-liter capacity tank. The system employs Research and Development method encompassing requirement analysis, design, implementation, and testing. Implementation results demonstrate the system successfully reads water level changes in real-time through OLED and local web dashboard based on SPIFFS. Testing across various water height conditions shows an average measurement error of 1 cm with response time of 1-2 seconds. The system classifies water conditions into Empty, Filled, and Full with appropriate buzzer response. Local web server implementation enables the system to operate independently without external server, making it effective for small-scale water tank applications.